2022
DOI: 10.3390/app12157707
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Investigation of Sound Radiation from Functionally Graded Thin Plates Based on Elemental Radiator Approach and Physical Neutral Surface

Abstract: This paper analyzes the sound radiation behavior of a clamped thin, functionally graded material plate using the classical plate theory and Rayleigh Integral with the elemental radiator approach. The material properties of the plate are assumed to vary according to the power-law distribution of the constituent materials in the transverse direction. The functionally graded material is modeled using a physical neutral surface instead of a geometric middle surface. The effects of the power-law index, elastic modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…A recent study has been performed on composite recycled glass bead panels sandwiched between two fiberglass composite sheets to evaluate the appropriateness for built environment and construction industry applications, particularly for loud built-up situations where they could be used as physical structural parts that could propose sound attenuation, or they could be utilized to reduce outdoor sound as noise screeners [22]. The classical plate theory and Rayleigh integral with the elemental radiator method were applied to analyze the acoustic radiation behavior of constrained thin functionally graded plates; it was found that the different values of the damping values could not significantly impact the acoustic radiation efficiency [23]. A mathematical model combining the classical forced plate theory with the combination of Green's function was presented to analyze the stress of thin plates and their vibration modes at different eigenfrequencies [24].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has been performed on composite recycled glass bead panels sandwiched between two fiberglass composite sheets to evaluate the appropriateness for built environment and construction industry applications, particularly for loud built-up situations where they could be used as physical structural parts that could propose sound attenuation, or they could be utilized to reduce outdoor sound as noise screeners [22]. The classical plate theory and Rayleigh integral with the elemental radiator method were applied to analyze the acoustic radiation behavior of constrained thin functionally graded plates; it was found that the different values of the damping values could not significantly impact the acoustic radiation efficiency [23]. A mathematical model combining the classical forced plate theory with the combination of Green's function was presented to analyze the stress of thin plates and their vibration modes at different eigenfrequencies [24].…”
Section: Introductionmentioning
confidence: 99%